Effects of Fermented Soybean Hulls on Reproductive Performance, Blood Physiology and Immune Parameters Along with Fecal Microbiota in Sows - Xiuguo Shang; Yingjie Cui; Chaoyue Shang; Kaiguo Gao; Yujuan Chen; Yaodong Quan (Animals)
This study aims to investigate the effects of fermented soybean hulls (FSHS) on reproductive performance, plasma biochemical profiles, immune parameters, and fecal microbiota in sows. A total of 325 sows were randomized into five groups, each fed a diet with varying FSHS proportions: 0% (control), 2% (FSHS2), 4% (FSHS4), 6% (FSHS6), and 8% (FSHS8). Diets were prepared by replacing conventional soybean hulls with FSHS in equal amounts. The study lasted from day 30 to day 110 of gestation. The results indicated the following: (1) Reproductive Performance: The number of live piglets per litter, newborn litter weight, and individual piglet weight increased linearly with the increase in FSHS addition in the diet (PLinear < 0.05). A trend toward reduced farrowing duration was observed when FSHS was added to the diet (PLinear = 0.076). FSHS improved newborn weight and weight variation compared to the control when FSHS was added to the diet (PAnova < 0.05). Replacing soybean hulls with FSHS also increased fecal scores, enhancing fecal consistency and alleviating constipation (p < 0.01). (2) Plasma Biochemical Indicators: Plasma urea concentration on day 60 decreased linearly with increasing FSHS (PLinear < 0.05). Plasma total protein and aspartate aminotransferase (AST) activities showed quadratic effects (PQuadratic < 0.05) on day 60 and 90 of gestation, while alkaline phosphatase activity on day 90 showed a quadratic trend (PQuadratic = 0.082). (3) Hormone Levels: Plasma insulin and adrenaline levels exhibited quadratic effects on day 60 and 90 of gestation, respectively (PQuadratic < 0.05). (4) Immune Parameters: Plasma immunoglobulin G (IgG) and M (IgM) levels increased linearly with FSHS proportion on day 60 (PLinear < 0.05), but no significant changes were observed on day 90 (p > 0.05). (5) Fecal Microbiota: On day 90, the abundance of actinobacteriota increased quadratically with FSHS levels (PQuadratic < 0.05), while bacteroidota decreased linearly (PLinear < 0.05). During parturition, actinobacteriota abundance continued to increase linearly (PLinear < 0.05). Notably, the FSHS8 group had higher actinobacteriota abundance compared to the control group (p = 0.05). At the genus level, terrisporobacter showed a quadratic increase and then decrease (PQuadratic < 0.05), while ruminococcus showed a quadratic decrease and then increased (PQuadratic < 0.05). Both terrisporobacter in the FSHS2 and FSHS6 groups and ruminococcus in the FSHS8 group were more abundant compared to the control (p < 0.01). Conclusions: Dietary supplementation with FSHS increased fecal microbial diversity, alleviated the incidence of constipation, and ultimately improved sow reproductive performance. The recommended optimal addition of FSHS to the sow diet is 6%.